2022
DOI: 10.3390/antiox11112208
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Profiling of Two Saudi Arabia Catalase Genes from Wheat and Barley in Response to Abiotic and Hormonal Stresses

Abstract: Catalase is a crucial enzyme in antioxidant defense systems protecting eukaryotes from oxidative stress. These proteins are present in almost all living organisms and play important roles in controlling plant responses to biotic and abiotic stresses by catalyzing the decomposition of H2O2. Despite their importance, little is known about their expression in the majority of monocotyledonous species. Here, we isolated and characterized two novel catalase genes from Triticum turgidum and Hordeum vulgare, designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
2
3
1
Order By: Relevance
“…Om Rabiaa, a local Tunisian variety) is highly expressed in the whole plant at all developmental stages [ 13 ]. The same findings were observed in the Waha ecotype, a Saudi variety [ 14 ], and in Triticum monococcum [ 15 ]. Moreover, TdCAT1 is regulated by bivalent cations and by the calcium/Calmodulin complex [ 16 ].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Om Rabiaa, a local Tunisian variety) is highly expressed in the whole plant at all developmental stages [ 13 ]. The same findings were observed in the Waha ecotype, a Saudi variety [ 14 ], and in Triticum monococcum [ 15 ]. Moreover, TdCAT1 is regulated by bivalent cations and by the calcium/Calmodulin complex [ 16 ].…”
Section: Introductionsupporting
confidence: 78%
“…Gene expression is controlled by the complex interaction of different cis-acting elements and trans-acting factors that participate in different pathways [ 26 ]. Previous investigations have confirmed that catalase genes could be induced by different treatments, such as salt stress [ 14 , 16 ], cold [ 10 , 29 , 37 ], drought [ 7 , 14 , 16 , 29 , 37 , 38 ], ABA [ 7 , 14 , 16 , 28 , 38 ], SA [ 16 ], and light [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of expected signal peptides and transmembrane regions indicates that these proteins are non-secreted rather than membrane-bound. Interestingly, none of the discovered CAT proteins had a transmembrane domain, contrary to prior findings for several CAT proteins, such as SlCAT1 in tomato [ 46 ], TtCAT1, and HvCAT1 [ 47 ]. A similar outcome was also noted in durum wheat [ 13 ], but in oat, all discovered CAT proteins lacked a transmembrane region, except for AvCAT5 [ 14 ].…”
Section: Discussioncontrasting
confidence: 63%